The Existence of Madura Local Food Commodity-Based Microbusinesses - Triyasari, Sri Ratna; Prastika Destiarni, Resti (SOCA: Jurnal Sosial Ekonomi Pertanian, 2023)
The importance of the existence of a business is to survive and have competitiveness in the midst of the current Covid-19 pandemic. The problem that is often faced by microbusiness in Bangkalan is that their strengths are less able to overcome weaknesses and threats. This study aims to determine the existence of microbusiness which will further produce strategic recommendations for survival. This research is through descriptive analysis, the variables studied are described. While qualitative analysis is used in assessing data sources, data reduction, and drawing conclusions which are analyzed using multiple linear regression analysis and SWOT. The results show that existence is influenced by purchasing power, product availability, and regulation. While the resulting strategic recommendations are not to increase production and inventory volumes during the pandemic, to create alternative income, to create alternative sales mechanisms, not to aggressively expand business, and to collaborate with banks as strategic partners for sources of financing, information, and business development.